The protection of confidential communication between a lawyer and a client in the case law of the European Court of Human Rights - Đukić Dimitrije (Bar Association of Vojvodina, Novi Sad, 2021)
Confidentiality of communication is a very important human right that gains in importance when the communication is conducted between a lawyer and a client. Namely, for a lawyer to be able to adequately represent their client, the client must be sure that the information they entrust to the lawyer will not reach third parties, i.e. that the communication will remain confidential. In this sense, protecting the confidentiality of communication between a lawyer and a client is very important not only for representing the client in each case, but also for the proper functioning of the legal system. This paper aims to establish which articles of the European Convention protect the right to a confidential communication between a lawyer and a client and how this communication is protected in practice by the European Court of Human Rights. The paper also examines whether it is possible to prescribe a measure by which such an important right as the right to privileged and confidential communication between a lawyer and a client could be limited and if so under what conditions.